2021
DOI: 10.1007/s00261-020-02941-5
|View full text |Cite
|
Sign up to set email alerts
|

Visual abstract for Abdominal Radiology: what it is, why we need it and how to make it

Abstract: The visual abstract is a short visual summary of the paper's key points. There are two main characteristics of the visual abstract. First, it should be brief and convey just the most relevant message of the paper. The visual abstract is not expected to be a comprehensive synopsis of the paper, but rather it is designed to allow the reader to skim through multiple abstracts to grasp the key findings. The visual abstract should also be self-explanatory. Its main objective is to engage the reader's interest in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…La conclusión es incluida en un recuadro dentro de la parte inferior 12 . Por su parte, Brook et al 1 emplean por no dividir esta sección media y solo añadir los resultados.…”
Section: Figura 1 Estructura Propuesta Para Un Resumen Visualunclassified
“…La conclusión es incluida en un recuadro dentro de la parte inferior 12 . Por su parte, Brook et al 1 emplean por no dividir esta sección media y solo añadir los resultados.…”
Section: Figura 1 Estructura Propuesta Para Un Resumen Visualunclassified
“…In the last decade, we have witnessed an unprecedented explosion in the use of newer methods to disseminate research findings to the medical community. Medical journals are no exception, and many have incorporated a new component to the published research article: the visual or graphical abstract 1–3 …”
Section: Figurementioning
confidence: 99%
“…It is also designed to provide readers with an instant understanding of articles (Ibrahim, 2018; Ramos & Concepcion, 2020). Currently, GAs have been adopted by lots of journals (Brook et al, 2021; Hendges & Florek, 2019). Yoon and Chung (2017) found that since the first GA was introduced in social sciences journals published by Elsevier in 2010, an increase with 350% of the use of GAs was observed during the period from 2011 to 2015.…”
Section: Introductionmentioning
confidence: 99%